Peningkatan Pemahaman Pendidikan Seksual melalui Permainan Ular Tangga di Taman Kanak-Kanak - Mamluatul Lu’lu’a (GHULAMUNA: JOURNAL OF EARLY CHILDHOOD EDUCATION, 2023)
The research aims to: 1) determine children's understanding of sexual education before the implementation of the "snake and ladder" game, 2) implement the "snake and ladder" game to enhance children's understanding of sexual education, and 3) assess the improvement in children's understanding of sexual education after the implementation of the "snake and ladder" game in Group B of TK PGRI Dasuk Sumenep during the Academic Year 2022/2023. The type of research used is Classroom Action Research (CAR) with the action research model from Kemmis and Taggart. The research consists of two cycles, preceded by an initial observation known as pre-action. The research findings indicate that the "snake and ladder" game can improve children's sexual understanding. The improvement in children's sexual understanding is evident from the pre-action phase, Cycle I, and Cycle II. In the pre-action phase, there was a 0% score. In Cycle I, the score was 25%, while in Cycle II, it increased to 92%. There was a 50% increase in the percentage of children's understanding of sexual education from pre-action to Cycle I, and a further 42% increase from Cycle I to Cycle II.